Sodium Dodecyle Sulphate Injection as a Secondary Oil Recovery Method - Saleh, Talib (Iraqi Journal of Science, 2023)
Sodium Dodecyle Sulphate (CH3(CH2)11SO4-Na+) solution was used as a secondary oil recovery by using a lab Model shown in figure-1. The effect of (solution concentration, temperature and salinity) on interfacial tension figure-2 and figure-3 and figure-4 respectively. The best values of these three variables, were taken (those values that give the lowest interfacial tension). Porosity, saturation, permeability were determined in the lab depending on Darcy law. Primary oil recovery was displaced by water until no more oil is obtained then sodium dodecyle sulphate solution was injected. The total oil recovery was 94.8% or 85.7% of the residual oil (secondary oil recovery) figure-5. This method was applied on Iraqi oil field and it gave results close to those obtained in lab model.